Why Do Seafarers Consider Leaving? Perceived Organizational Support And Turnover Intention In Maritime Human Resource Management: A Systematic Literature Review - Muh Nurfadel Hamzah; Muhaidir Ikram (Institute of Advanced Knowledge and Science, 2026)
Turnover intention among seafarers is a strategic challenge for the global maritime industry, particularly for Indonesia, one of the major suppliers of maritime labor. Indonesian seafarers are vulnerable to turnover intention because maritime work is commonly characterized by contract-based employment, prolonged family separation, psychological isolation, occupational hazards, limited welfare support, and uncertain career pathways. Although previous studies have examined seafarers’ well-being, fatigue, job satisfaction, and retention, limited systematic evidence has integrated perceived organizational support (POS), turnover intention, and Indonesian seafarers within the perspective of Maritime Human Resource Management (MHRM). This article presents a Systematic Literature Review conducted according to PRISMA 2020 guidelines. Relevant literature was identified from Scopus, Web of Science, ScienceDirect, Emerald, SpringerLink, Taylor & Francis, Wiley Online Library, SAGE Journals, PubMed, Google Scholar, Garuda, and SINTA. Guided by Organizational Support Theory, the review synthesizes evidence across seven themes: organizational support and seafarer retention, job satisfaction, organizational commitment, work-family conflict, welfare and safety support, career development, and MHRM retention practices. The findings show that higher perceived organizational support is consistently associated with lower turnover intention through increased job satisfaction, stronger organizational commitment, psychological well-being, and trust in the organization. Turnover intention among Indonesian seafarers is therefore not merely an individual decision, but a systemic outcome shaped by organizational support, contract fairness, welfare provision, safety protection, and career opportunities. The study extends Organizational Support Theory to the maritime context and offers practical guidance for shipping companies, crewing agencies, maritime HR managers, and Indonesian regulators in strengthening seafarer retention strategies.